The Japanese experience : - Beasley, W. G. (Los Angels,University of California Press, 1999)
The Japanese Experience is an authoritative history of Japan from the sixth century to the present day. Only a writer of W.G. Beasley's stature could render Japan's complicated past so concisely and elegantly. This is the history of a society and a culture with a distinct sense of itself, one of the few nations never conquered by a foreign power in historic times (until the twentieth century) and the home of the longest-reigning imperial dynasty that still survives. The Japanese have always occupied part or all of the same territory, its borders defined by the sea. They have spoken and written a common language, (once it had taken firm shape in about the tenth century) and their population has been largely homogeneous, little touched by immigration except in very early periods. Yet Japanese society and culture have changed more through time than these statements seem to imply. Developments within Japan have been greatly influenced by ideas and institutions, art and literature, imported from elsewhere. In this work Beasley, a leading authority on Japan and the author of a number of acclaimed works on Japanese history, examines the changing society and culture of Japan and considers what, apart from the land and the people, is specifically Japanese about the history of Japan.